PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARANIPA DENGAN MENGGUNAKAN PENDEKATAN INKUIRI DI SEKOLAH DASAR - Wahyuni, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research early from fact in SD Islam Ibnu Syam  Kubang Putiah that student still difficulty in comprehending the concept IPA because not yet used approach of correct study.For it was held a class action research, which aims to describe the learning results with experimental method using IPA.Lesson plan first cycle was 69.5% in the second cycle to 89%.Implementation of the aspects of the teacher's first cycle was 69.5% in cycle II to 88.5% and on aspects of students' first cycle was 65.5% in the second cycle to 84.5%. Themean results of learning studernts (cognate, afective and psychomotor) cycle I learning outcomes 68,87 experience step-ups on the second cycle 80,87 . Kata Kunci  :  hasil belajar, IPA, pendekatan, pembelajaran, dan pendekatan  inkuiri